Analisis Kesulitan Siswa dalam Menyelesaikan Soal Perkalian Bersusun Kelas IV-A SDN Sukarame - Ariyani, Desi; Zahrah, Riza Fatimah; Sidik, Geri Syahril (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to identify the types of difficulties students face and the underlying factors contributing to these challenges in solving stacked multiplication problems. This research is descriptive with a qualitative approach involving six fourth-grade students, selected based on their ability levels (high, medium, low) from test results. Data collection techniques include tests, observations, interviews, and documentation. The data analysis techniques used in this study are data reduction, data display, conclusion, and verification. The research findings indicate that students experience difficulties in aspects of concepts and principles (procedural). Conceptual difficulties include mistakes in calculating multiplication results and retaining numbers, while procedural difficulties are shown by incomplete working steps and inaccuracy in adding retained numbers. The causes of these difficulties include internal factors, such as a low mastery of basic multiplication, understanding of place value concepts, and the procedure for column multiplication, as well as external factors in the form of teaching methods from teachers that are not yet fully effective. Students' difficulties in solving multi-step multiplication problems are caused by a weak understanding of concepts and systematic working procedures, hence a more concrete and repetitive learning approach is needed. Strategies that can be applied to minimize students' difficulties include the use of the finger math method, Dienes block manipulatives, as well as providing regular and gradual exercise problems.